Photograph registration of petri dishes in high quality and image editing of microbiological assays - Rodrigues, Cleverson [UNESP]; David, Grace Queiroz [UNESP]; dos Reis, André Rodrigues [UNESP] (Springer Nature, 2022)
Science is based on evidence that can be measured or observed through methodical techniques which are expressed in several ways, either quantitatively or qualitatively. Technical photograph becomes one of the most important key tools to disclose experimental results. In microbiological research, several pieces of evidence can be indicated with parameters that are deeply related to culture media; pH and color variation, halo formation, overlay of structures, culture shape, among others. The employment of technical photographs as a strategy of the experimental observation and reliable representation is indispensable. The protocol presented here suggests the production of photographic support in microbiological assays in Petri dishes taken by smartphone to obtain high-quality images, besides showing tools to edit images using PowerPoint. The support is composed of a paper tube with a transparent border, whose reduced light penetration avoiding light reflection over the Petri dishes or the culture media. The edition consists of photograph variation, and in clipping and pasting on uniform backgrounds to provide further detailing. The protocol allowed a standardized photograph collection in high quality, which is ideal for a comparative portrait of microbiological behaviors. The image editing enabled a framework and greater visibility of physical and biological structures in the exhibition of photographs inside the manuscript, such as the removal of noises, background alterations, deformities or irregularities. This protocol is an intelligent and cheap tool to help researcher on the knowledge-obtaining process, and it is applied to different experiments or adapted into the most variable research subjects.
Keywords: Bioasseyes; Microbiology; Protocol; Technical Photograph